Analysis of Packaging Standards and Criteria of Goods Conditions Towards The Accuracy of Goods Receipt on The Tokopedia Application - Kusumaningrum, Stefani Putri Ayu; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The rapid development of the e-commerce industry in Indonesia, especially Tokopedia, has driven the importance of logistics management, including packaging and receiving goods, in maintaining customer satisfaction . The purpose from study This is to analyze the influence of packaging standards and criteria for the condition of goods on the accuracy of receiving goods in warehouses served by Tokopedia. The research methodology used is qualitative and using approach fish bones or fishbone diagram to identify factors causing damage to goods in the packaging and receiving process. The results of the study indicate that human factors, methods, machines, materials, environments, and measurements have a significant role in damage to goods. Packaging standards implemented by Tokopedia, such as the use of proper packaging and clear packaging procedures, can minimize damage to goods during shipping. This study also provides recommendations for improving packaging training, stricter supervision of goods receipt, and improving the quality of packaging materials. Thus, the accuracy of receiving goods according to packaging standards is very important to ensure customer satisfaction and smooth e-commerce operations at Tokopedia.